Investigating EFL students’ EAP needs on productive skills in Malaysian universities - Gholami, Reza; Noordin , Noreen; Mustapha, Ghazali (Universiti Putra Malaysia Press, 2013)
Many international students are currently pursuing their post-secondary studies in Malaysia. At the beginning of each study programme in Malaysian universities, international students typically attend EAP courses for a better performance on campus. However, it is believed that these courses do not satisfactorily meet the EFL international students’ needs, and this is probably because such courses do not take into consideration a comprehensive need analysis. This survey is one of the forerunning efforts to find out what tasks of English writing and speaking skills are actually needed by EFL international students in order to improve their ability of English as these two skills have been reported to be the most essential ones in academic settings. To this end, a Need Analysis questionnaire was employed to examine EFL international students’ needs over productive skills. The questionnaire was sent to respondents via email and 60 post-secondary students responded and returned the questionnaire. The data analysis revealed that the majority of the participants considered speaking as the most important language skill that they needed to improve. Also, they reported that Explaining Ideas, Giving a Presentation, Giving Reasons, and Discussing in Meetings ranked on top of their speaking needs. In addition, the most needed writing tasks in EAP classes included Taking Lecture Notes and Writing Journal Papers/Articles. Moreover, gender was found to be significant in determining speaking tasks needed by EFL international students. Finally, PhD students reported to have different speaking needs compared to students studying Master and Bachelor programmes. Findings of this study are majorly congruent with other studies on international students’ needs in academic settings, which can be of worth for the current EAP/ESP courses offered in Malaysia for EFL international students.